Effects of pressure and thickness on elastic and dielectric properties of chitosan - Mohd Hashim, Nurul Hazwani (2012)
This dissertation describes the effect of pressure on the elastic properties of chitosan and also the effect of thickness and pressure on electrical properties of chitosan. The powdered chitosan is being pressed into pellets and the elastic and electrical properties were studied. The experimental investigation was divided into two categories. The minor experimental work, which provides supportive evidence to elastic and electrical properties, consists of work on x-ray diffraction and FTIR. The main experiments consist of work on ultrasonic and electrical measurements. The electrical measurements were measured at low frequencies from 10-2 to 104 Hz while ultrasonic properties were determined with MATEC 8000 at 5MHz resonating frequency and at room temperature. The semicrystalline structure of the chitosan sample was evident by the XRD spectrum. Ultrasonic measurement is used as a non-destructive testing (NDT) technique in analyzing the physical of liquid and solid material. NDT is important because the properties of the sample can be tested without destroying or changing the physical properties of the sample. The elastic moduli, longitudinal modulus (L), shear modulus (G), Young’s modulus (E), bulk modulus (K) and Poisson’s ratio increase with increasing of pressure from 2.0 to 6.0 tonne. The large difference between L and G due to the volume effects shows that the materials formed are easier to bend than to be elongated. Electrical measurement of chitosan shows that sample with 4 mm thickness gives the highest value of ε’(ω) ~ 430 compared to 2 mm sample ε’(ω) ~ 140. And for chitosan pellets with different pressure, it can be observed that sample with 2.0 tonne pressed pressure gives the highest value of ε’(ω) ~ 429 compared to 6.0 tonne sample ε’(ω) ~ 229. The dielectric graphs were then normalized into a master curve and fit using the universal law to obtain the properties and mechanism that took part, with the parameters involved such as p, n and α. The entire fitted graph showed that chitosan consisted of quasi-dc and also dipolar mechanism. In complex impedance, the grain boundary effect that appears as a semicircle at low frequency is bigger than the high frequency bulk semicircle. There is no overlapping of peaks in the modulus and impedance plot which suggested that this sample is a long-range and localized relaxation.The activation energies obtained from the master plot, impedance and modulus spectroscopy studies on chitosan pellets with different pressure and thickness reveals the defect relaxation nature.